Assessment of the Viability of using 3D printing for the Design and Prototyping of Historical Artifacts as Replicas - Ruevan Evangelista Alboro; Leslie R. Jorge Acain; Cristina G. Rivera; Aaron Paul C. Rivera; Shiela Marie Roxas-Buce; Robert O. Aguilar; Ray Noel M. Delda; John Ryan C. Dizon (Universitas PGRI Semarang, 2022)
3D printing is now being used in many different applications. Souvenir items and replicas of artifacts, which usually do not need to have high durability/strength, may be one of the possible applications of 3d printing. In this study, the researchers tried to manufacture keychains, refrigerator magnets, and display items from historical artifacts in the province of Bataan. Three experts (1 from the tourism industry, 1 BS Tourism Faculty, and 1 expert in 3d printing) were tapped to assess the viability of using 3d printing in the production of souvenir items. The items were particularly evaluated based on their quality, color, surface finish, cost, durability, authenticity, material, etc. Important considerations were obtained from 3d printing as well as from the insights/evaluation provided by the experts. Experts suggested modifying the thickness, color, and materials for added appeal. Reducing the price might also increase the market for souvenir items. Adding labels and descriptions has also been recommended. All these improvements will inspire different emotions, create impact and make the design more memorable.